1998
DOI: 10.1111/j.1440-1746.1998.01550.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary report of a randomized, double‐blind placebo‐controlled trial of a Chinese herbal medicine preparation CH‐100 in the treatment of chronic hepatitis C

Abstract: The treatment of chronic hepatitis C is relatively unsatisfactory and many patients have turned to unproven alternative medicines to modify the course of their illness. We report a study of a Chinese herbal medicine preparation CH-100 in the management of chronic hepatitis C. Patients with documented chronic hepatitis C were randomly allocated to receive active herbal or placebo tablets (five tablets thrice daily). Patients were followed monthly and evaluated by a Western and a traditional Chinese medical prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 16 publications
0
35
1
Order By: Relevance
“…Similarly, cell culture work on interleukin-10 production in patients with chronic hepatitis C indicates that this may halt the progression of the disease 29 . Other work suggests a positive effect of another Chinese herbal preparation on the course of chronic hepatitis C 30 . Batey et al found a preparation containing as many as 19 different herbal extracts to be effective in reducing elevated alanine aminotransferase levels in patients with hepatitis C. However, no patient effectively cleared the virus 30 .…”
Section: Chinese Herbal Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, cell culture work on interleukin-10 production in patients with chronic hepatitis C indicates that this may halt the progression of the disease 29 . Other work suggests a positive effect of another Chinese herbal preparation on the course of chronic hepatitis C 30 . Batey et al found a preparation containing as many as 19 different herbal extracts to be effective in reducing elevated alanine aminotransferase levels in patients with hepatitis C. However, no patient effectively cleared the virus 30 .…”
Section: Chinese Herbal Medicinementioning
confidence: 99%
“…Other work suggests a positive effect of another Chinese herbal preparation on the course of chronic hepatitis C 30 . Batey et al found a preparation containing as many as 19 different herbal extracts to be effective in reducing elevated alanine aminotransferase levels in patients with hepatitis C. However, no patient effectively cleared the virus 30 . The frequency with which Chinese herbs evoke adverse effects in the liver is unclear since, so far, reports about toxicity have largely been case reports.…”
Section: Chinese Herbal Medicinementioning
confidence: 99%
“…In a double-blind, placebo-controlled trial involving patients with hepatitis C, treatment with the product was associated with a significant reduction in ALT levels, although no treated person cleared the virus. 43 NCCAM is currently supporting a study of a 10-herb combination, referred to as 3AR. The trial will assess safety and adverse events, as well as symptoms of fatigue, quality of life, liver function, and HCV-RNA levels in patients who do not qualify for standard therapy of hepatitis C. Thus, there is increasing interest in conducting rigorous testing of candidate CTM compounds (1) as alternatives to standard treatment, (2) to augment conventional treatments, or (3) to ameliorate the side effects of current therapies.…”
Section: Blended Herbal Formulations and Extractsmentioning
confidence: 99%
“…CH-100 183,184 CH-100 is a blend of 19 different herbs used in China to treat liver disease. It has immunomodulatory and anti-inflammatory effects.…”
Section: Agent and References Descriptionmentioning
confidence: 99%